An Investigation into Forming of Gears Using Rotary Forging Process - Abd-Eltwab, Ayman Ali; Elsyed Ayoub, Walid; El-Sheikh, Mohamed N.; Saied, Essam Khalaf; Ghazaly, Nouby M.; Gomaa, A. A. (Manufacturing Technology Journal, 2024)
Gears and toothed parts are significant components in power transmission systems. These parts usu-ally manufactured by traditional methods such as machining by milling or forming by rotary forging. In this study, the forming of solid gears or toothed parts using a forging process that combines rotary forging and ballizing technique. The specimens were placed inside the die with excessive volume to fill the toothed part in the die. The forming tool applies pressure to the specimen while rotating it together with the die by the lathe machine chuck, while the tool advances continuously in the direc-tion of the die. This reduces height of the specimen and increases its diameter, causing metal flow to fill die cavity teeth and form the gear or toothed part required for production. Two sets of experi-ments were performed. In the first set, optimization for the appropriate volume of four different sizes of dies and four forming tools was conducted. While in the second set, the effects of forming process variables on the forming load and tooth filling percentage was studied. The results showed that the best tooth filling ratio happened with specimens size of 1.2 to 1.4 times the volume size of the desired tooth for filling. The results also revealed that the forming speed, die size, and forming tool diameter affect the filling ratio and forming load.
Keywords: Forming of gears; Rotary forging; Externally splined; Ballizing technique; Filling ratio and process parameters